Preventing requirements defects to improve requirements engineering in information systems development / Mohd Farid Assamani Mohamed Zainon - Mohamed Zainon, Mohd Farid Assamani (2006)
There are lots of requirements defects that can delay the progress of development. It is also will give disaster on software product when it reaches on implementation phase. Even though it will interrupt the process, there are still some techniques that can help to prevent those requirements defects. This research is conducted to identify what are the commonly known requirements defects that occurred during the process and what are the techniques that can be used to prevent it. The objectives of this research are to compare each of the prevention techniques and proposing the effective prevention techniques that can be implemented. The research approach used is in a mixed method. Based on findings, 46 out of 50 respondents agreed that demand change is a most defect occurred, there are other defects that mostly occurred e.g., incomplete requirements, conflicting requirements, misimderstood requirements and inconsistent tacit. 35 respondents agreed that scenario was the best technique to prevent defects. While, there are some other techniques that also suitable to prevent defects, such as, user data model, focus groups with users and consistency review. From the propose techniques, it is conclude that the objectives are achieved.